Concordance between stages of behavior change questionnaire and IPAQ - Nakamura, Priscila Missaki [UNESP]; Papini, Camila Bosquiero [UNESP]; Teixeira, Inaian Pignatti [UNESP]; Sebastião, Emerson; Gobbi, Sebastião [UNESP]; Cordeira, Kelly Lynn; Kokubun, Eduardo [UNESP] (FapUNIFESP (SciELO), 2013)
A low rate of physical activity (PA) participation is observed worldwide. The identification of feasible and reliable instruments able to accurately measuring PA and help in the development of interventions to promote PA are necessary. This study aimed to analyze the concordance between the Stages of Behavior Change Questionnaire (SBCQ) and the International Physical Activity Questionnaire (IPAQ long-version) in assessing adult leisure-time physical activity (LTPA). A total of 1.588 adults completed the IPAQ to assess LTPA and the participants who performed more than 10 min/week were classified in active individuals. Using the SBCQ, active individuals were those classified in the action or maintenance stage and inactive individuals were those classified in the precontemplation, contemplation or preparation stage. The concordance between SBCQ and IPAQ was found to be 0.80. Separated by gender, it was observed a concordance between the two instruments of 0.82 for women, and 0.77 for men. Regarding age group, it was found to be 0.81 for young and middle-aged adults, and 0.77 for older people. The SBCQ presented a very good concordance with IPAQ to assess LTPA.
Keywords: Adults; Assessment of physical activity; Behavior toward physical activity; Elderly